(untitled) (Journal of Foreign Language Studies, 2024)
Given that students face many difficulties in developing French listening comprehension and the free and open access MOOC model has failed, this paper analyzes some factors affecting listening comprehension and some reasons why learners do not complete the MOOC course. From that basis, the author proposes designing activities for listening comprehension practice from authentic materials extracted on French media and integrating them into an online course model for a specific learner group called SPOC (small private online course) using Facebook groups as an e-learning platform.